Deciphering the conformational dynamics of gephyrin-mediated collybistin activation - Imam, Nasir; Choudhury, Susobhan; Hemmen, Katherina; Heinze, Katrin G.; Schindelin, Hermann (Biophysical Reports, 2022)
Efficient neuronal signaling depends on the proper assembly of the postsynaptic neurotransmitter machinery. The majority of inhibitory synapses feature γ-aminobutyric acid type A (GABAA) receptors. The function of these GABAergic synapses is controlled by the scaffolding protein gephyrin and collybistin, a Dbl family guanine nucleotide exchange factor and neuronal adaptor protein. Specifically, collybistin interacts with small GTPases, cell adhesion proteins, and phosphoinositides to recruit gephyrin and GABAA receptors to postsynaptic membrane specializations. Collybistin usually contains an N-terminal SH3 domain and exists in closed/inactive or open/active states. Here, we elucidate the molecular basis of the gephyrin-collybistin interaction with newly designed collybistin Förster resonance energy transfer (FRET) sensors. Using fluorescence lifetime-based FRET measurements, we deduce the affinity of the gephyrin-collybistin complex, thereby confirming that the C-terminal dimer-forming E domain binds collybistin, an interaction that does not require E domain dimerization. Simulations based on fluorescence lifetime and sensor distance distributions reveal at least a two-state equilibrium of the SH3 domain already in the free/unbound collybistin, thereby illustrating the accessible volume of the SH3 domain. Finally, our data provide strong evidence for a tightly regulated collybistin-gephyrin interplay, where, unexpectedly, switching of collybistin from closed/inactive to open/active states is efficiently triggered by gephyrin.
CRIS-Team Scopus Importer:2023-03-23